Telling Stories about Transformed Identity of Mithila Women through Paintings - Neupane, Pimala (Khwopa Journal, 2024)
This research paper attempts to explore the way Maithili women project their identiy by telling their stories in Mithila Paintings. They portray their role as women telling traditional to extraordinary stories through painting in the Maithil community. On the one hand, they have social role to play as daughter (in-laws) and mother (in-laws), and remain confined to serve the overall purposes of the patriarchal ruling system, follow conventional set of behaviors in the family and society, but on the other hand, they hold tremendous skills of telling stories executing Mithila paintings.  This art and skills in them have finally helped them to carve out their identity as independent, bold, and courageous women leading the whole Mithila community by telling their story in Mithila painting. They present their long experience of struggle of fighting against their marginal position in the Maithil community.  During the research on Mithila women’s paintings, the researcher hascollected data based on secondary resources such as articles, books, different research works of the different researchers from online or printed materials, visiting libraries, and consulting with experts in the field.  The visual storytelling method is used and feminist theory is applied to analyze the data and to support her claim.